Touch-Avoidance and Touch-Seeking in Non-intimate Relationships: The Null Effects of Sightedness. (September 2021) - Sorokowska, Agnieszka; Stefańczyk, Michal Mikolaj; Płachetka, Justyna; Dudojć, Olga; Ziembik, Krzysztof; Chabin, Dominika; Croy, Ilona
People differ in their touch preferences and in the ways in which they touch others. People who are blind are particularly sensitive to tactile stimulation as a result of sensory compensation, and sense of touch can support their interpersonal communication. In the article presented here, we aimed to explore whether visual status predicts preferences for touch behaviors involving strangers; specifically, we examined touch-seeking and touch-avoidance in non-intimate interpersonal situations. Our study, whose participants comprised 43 individuals with congenital blindness, 53 individuals with adventitious blindness, and 47 sighted controls, showed that visual status does not predict touch-seeking or social touch-avoidance. We also observed similar gender differences in all participating groups, with women avoiding social touch more than men in non-intimate interpersonal situations involving strangers.